Faith Diplomacy and Conflict Resolution; A Case Study of Morocco and West African Countries - Ahmed HAMZAOUI, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2022)
Religions have often been a divisive factor of leading to conflicts in many parts of the world. In recent times, suffices to mention Bosnia, Northern Ireland, Southeast Asia, and the Middle East. Yet, Religion can also play a constructive role in consolidating peace and resolving conflicts. This article examines expectations of faith dialogue and how conflict can change to peace process building because of this soft power tool; the focus here is on the western block of Moroccan Sahara vs. the separatist group called Polisario driven by the support of the Algerian Republic. Three approaches are used in faith dialogue mainly theological, political and peace building. All will be discussed in this article. The Moroccan case in managing domestic religious issues in some African countries can have tremendous results in achieving foreign policy goals. Unlike other cases of foreign religious sphere, the Moroccan case has attracted attention of both academia and researchers since it advanced Morocco’s economic and geopolitical stability and addressed the issue of the western block of the Moroccan Sahara in order to find a resolution for this protracted conflict in the area.. The last segment of the paper will focus on shared practices of religious dialogue as a tool of peace making through examining the role of some religious institutions and brotherhood communities. The article concludes that faith dialogue can contribute to peace building and harmony.